Comparison of antimicrobial resistance patterns of enterotoxin gene positive and negative Bacteroides fragilis isolates [Enterotoksin geni pozitif ve negatif Bacteroides fragilis izolatlarinin antibiyotiklere direnç durumlarinin karşilaştirilmasi] - (:unkn) unknown (My University, 2005)
Some of the Bacteroides fragilis strains produce enterotoxin named fragilysin which is accepted as a virulence factor. In this study, the presence of enterotoxin genes (bft) in clinical B.fragilis strains has been investigated and the antimicrobial resistance patterns of bft positive and negative isolates have been compared. B.fragilis strains isolated from different clinical samples were identified by conventional methods and API 20A system, and the presence of bft genes were searched by using BF3/BF4 primers in polymerase chain reaction. A total of 100 B.fragilis strains of which 50 bft gene positive and 50 bft gene negative were included to the study, and their antimicrobial susceptibilities were determined by agar dilution method as recommended by NCCLS (M11-A4). Of 100 strains, 71 (34 bft negative, 37 bft positive) have been isolated from the stool, and 29 (16 bft negative, 13 bft positive) have been isolated from other specimens (blood, abscess, pleural and peritoneal fluids). β-lactamase production was detected in 96% of enterotoxigenic B.fragilis (ETBF) and 95% of non-toxigenic strains, and all tested strains were found to be susceptible to amoxicillin/clavulanic acid, imipenem and metronidazole. The resistance rates (with MIC90 values) of bft positive isolates against the other antibiotics were as follows; 96% (256 μg/ml) for ampicillin, 16% (256 μg/ml) for piperacillin, 8% (32 μg/ml) for cefoxitin, 24% (>256 μg/ml) for clindamycin, 74% (64 μg/ml) for tetracycline and 0% (8 μg/ml) for chloramphenicol. These rates were found as follows for bft negative strains; 95% (256 μg/ml) for ampicillin, 6% (64 μg/ml) for piperacillin, 6% (32 μg/ml) for cefoxitin, 38% (>256 μg/ml) for clindamycin, 64% (64 μg/ml) for tetracycline and 4% (8 μg/ml) for chloramphenicol. Although the resistance rates and MIC90 values of bft positive strains against the antimicrobials seemed to be higher, there were no statistically significant differences between resistance rates of bft positive and negative strains (P>0.05; 0.12 and 0.28, respectively).
Keywords: Antimicrobial susceptibility; Enterotoxigenic Bacteroides fragilis; Fragilysin